1995
DOI: 10.1002/mrd.1080420408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cumulus cells and follicle‐stimulating hormone during in vitro maturation on parthenogenetic activation of bovine oocytes

Abstract: The response to parthenogenetic activation (calcium ionophore A23187) of bovine oocytes after 30 hr of culture in different maturation conditions was evaluated. The activation rates of oocytes in response to 10 mu M A23187 were similar (86% +/- 4 vs. 89% +/- 8) when the oocytes matured with or without cumulus cells were cultured in TCM-199 + 10% fetal calf serum (maturation medium [MM]) alone. However, the activation rates were significantly lower in oocytes matured with than without cumulus cells (48 +/- 10 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 42 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, pig eggs are entirely dependent upon stored maternal mRNA for support during this period (Jarrell et ah, 1991). In the present study, cleavage of parthenotes did not proceed beyond the four-cell stage in both groups, probably due to both the activation procedure and the culture conditions, which can affect parthenogenetic activation rates (Hagen et ah, 1991;Funahashi et ah, 1994;Chian and Sirard, 1995). Until normal young are produced, the possibility that irradiation and the presence of damaged DNA has some adverse effects on cleavage at later stages of development cannot be ruled out.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, pig eggs are entirely dependent upon stored maternal mRNA for support during this period (Jarrell et ah, 1991). In the present study, cleavage of parthenotes did not proceed beyond the four-cell stage in both groups, probably due to both the activation procedure and the culture conditions, which can affect parthenogenetic activation rates (Hagen et ah, 1991;Funahashi et ah, 1994;Chian and Sirard, 1995). Until normal young are produced, the possibility that irradiation and the presence of damaged DNA has some adverse effects on cleavage at later stages of development cannot be ruled out.…”
Section: Discussionmentioning
confidence: 81%
“…Further, we have shown that PCB toxicity in bovine oocytes is related to a reduced competence of the oocytes to undergo normal cytoplasmic maturation, as indicated by an abnormal migration of cortical granules during maturation and subsequent fertilization and by changes in the polyadenylation pattern of several maternal mRNAs (Pocar et al 2001a). Because cumulus cells play an important role in the nuclear and cytoplasmic changes associated with oocyte maturation (Larsen & Wert 1988, Mattioli et al 1988, Fukui 1990, Chian & Sirard 1995, Tanghe et al 2003, in the present study we decided to investigate whether cumulus cells can modulate the adverse reproductive effects of environmental toxicants.…”
Section: Discussionmentioning
confidence: 99%
“…The CCs provide the nutrients and the regulatory signals upon which the oocytes are dependent, and these elements play very crucial roles in the maturation of oocytes cytoplasm and nucleus; in this way, developmental competence is acquired. (Chian and Sirard, 1995;Gilchrist et al, 2008). It has been shown that when CCs are removed at early stage of IVM from oocytes or before the IVF, the rates of maturation, cleavage, and blastocyst formation are reduced.…”
Section: Introductionmentioning
confidence: 99%